2014
DOI: 10.1002/iid3.37
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lasofoxifene and bazedoxifene on B cell development and function

Abstract: The third generation selective estrogen receptor modulators lasofoxifene (las) and bazedoxifene (bza) are indicated for treatment of postmenopausal osteoporosis. 17β-Estradiol (E2) and the second generation SERM raloxifene (ral) have major effects on the immune system, particularly on B cells. Treatment with E2 or ral inhibits B lymphopoiesis and treatment with E2, but not ral, stimulates antibody production. The effects of las and bza on the immune system have not been studied. Therefore, the aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
3
26
2
Order By: Relevance
“…In fact, in human males made hypogonadal and selectively replaced with either estrogen or testosterone, estrogen is associated with an increase in the percentage of bone marrow CD19 + B cells (40)(41)(42)(43). In our study, we found that ovariectomy induced an increase in CD19 + and B220 + B cells, but BSNXD treatment decreased B cell numbers in the BSNXD+OVX group.…”
Section: The Controversial Role Of B Cells On Bonesupporting
confidence: 42%
“…In fact, in human males made hypogonadal and selectively replaced with either estrogen or testosterone, estrogen is associated with an increase in the percentage of bone marrow CD19 + B cells (40)(41)(42)(43). In our study, we found that ovariectomy induced an increase in CD19 + and B220 + B cells, but BSNXD treatment decreased B cell numbers in the BSNXD+OVX group.…”
Section: The Controversial Role Of B Cells On Bonesupporting
confidence: 42%
“…The higher number of IgM þ cells observed in naïve and hemocyaninstimulated head kidney leukocytes from Tmx-treated fish during the recovery period would suggest a pivotal role for this compound in the homeostasis of the immune responses. However, further studies will be necessary to gain a deeper understanding of the mechanism underlying the immunotoxicology effects caused by this compound in this cell type in fish taking into account that E 2 , but not SERMs, increased the Ig production and the number of Igproducing cells in the bone marrow and spleen (Bernardi et al, 2014;Erlandsson et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…In mammals five antibody isotypes have been identified (IgA, IgD, IgE, IgG and IgM), while in fish IgM has been identified as the most common Ig in the serum of teleosts, although IgD (Hordvik et al, 1999;Stenvik and Jorgensen, 2000;Wilson et al, 1997), IgT/IgZ (Hansen et al, 2005;Ryo et al, 2010) have also been identified. It has been previously demonstrated that natural and synthetic estrogens, including SERMs, have major effects on the immune system, particularly on B cells (Bernardi et al, 2014). In gilthead seabream it has been previously demonstrated that total IgM levels decreased at 3 and 7 days after E 2 post-injection (Cuesta et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…It has previously been shown that mice treated with E2 in doses similar to the one used here obtain serum E2 levels corresponding to low diestrus levels (10-25 pg/ml) (Offner et al, 2000). The doses of ral, las and bza, were chosen based on our previous finding that they cause a significant increase in total bone mineral density in ovx mice (Bernardi et al, 2014). In addition, body surface area calculations ensured that doses of ral, las and bza used in mice were similar to those used in humans (Reagan-Shaw et al, 2008).…”
Section: Hormones and Treatmentmentioning
confidence: 99%
“…Interestingly, preliminary data from our lab show that also las and bza have beneficial effects on disease development and associated bone loss in postmenopausal collagen-induced arthritis (Andersson et al, submitted). We recently reported that las and bza inhibit B lymphopoiesis at a later developmental stage compared to E2, and that they do not increase the number of antibody-producing cells or the marginal zone B cell population (Bernardi et al, 2014). However, no previous studies have explored the effects of las and bza on T cell development.…”
Section: Introductionmentioning
confidence: 98%